CIRCUIT TRAINING REDUCES CARDIOMETABOLIC RISK FACTORS IN WOMEN - Zanina,Gustavo Osório (2023)
ABSTRACT Introduction Combined training is more effective than an isolated modality in reducing cardiometabolic risk indicators. Objective To evaluate the effect of circuit training volume on anthropometric and biochemical risk indicators for cardiometabolic diseases in overweight women. Methods Thirty-two participants underwent 24 weeks of circuit training with free weights combined with aerobic exercise. The training volume during the 24 weeks was used to distribute the women into moderate-volume physical activity (MVA), low-volume physical activity (LVA) and control (CON) groups. Anthropometric indices (body mass, body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR)), blood glucose, insulin, insulin resistance (HOMA-IR), total cholesterol (TC), triglycerides, HDL-c, and LDL-c were evaluated at the beginning of the program and after 12 and 24 weeks. Results There was no interaction between training volume and time for any of the variables studied, but the intervention time influenced body mass (p=0.013) and BMI (p=0.012), and there was a tendency for participation time to reduce body mass (p=0.063) and BMI (p=0.062) after six months of intervention. The volume of the physical activity affected HDL-c (p=0.037), being significant (p=0.030) in the comparison between the MVA and CON groups. Additionally, there was a downward trend in HDL-c after six months of intervention (p=0.073), with a smaller reduction observed in the MVA group, indicating a protective role of moderate physical activity in the reduction of this lipid fraction. The association between physical activity volume and participation time resulted in a clinical improvement in total cholesterol (χ2 = 5.453, p = 0.02), with a higher probability of reaching clinically adequate values in the MVA group (OR = 0.126; 95%CI 0.019 - 0.827). Conclusion Training volume improved cardiometabolic risk factors in overweight women. Level of evidence II; Therapeutic Studies - Investigating the Results of Treatment.